At Westonci.ca, we connect you with the best answers from a community of experienced and knowledgeable individuals. Explore thousands of questions and answers from a knowledgeable community of experts on our user-friendly platform. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
To find the inverse of the function [tex]\( f(x) = (x - 2)^3 \)[/tex], we will follow a step-by-step algebraic approach.
### Steps to Find the Inverse Function:
1. Replace [tex]\( f(x) \)[/tex] with [tex]\( y \)[/tex]:
[tex]\[ y = (x - 2)^3 \][/tex]
2. Solve for [tex]\( x \)[/tex] in terms of [tex]\( y \)[/tex]:
[tex]\[ y = (x - 2)^3 \][/tex]
3. To isolate [tex]\( x \)[/tex], take the cube root of both sides:
[tex]\[ \sqrt[3]{y} = x - 2 \][/tex]
4. Solve for [tex]\( x \)[/tex]:
[tex]\[ x = \sqrt[3]{y} + 2 \][/tex]
5. Replace [tex]\( y \)[/tex] with [tex]\( x \)[/tex] to write the inverse function:
[tex]\[ f^{-1}(x) = \sqrt[3]{x} + 2 \][/tex]
### Conclusion:
The inverse of the function [tex]\( f(x) = (x - 2)^3 \)[/tex] is:
[tex]\[ f^{-1}(x) = \sqrt[3]{x} + 2 \][/tex]
So the correct answer from the given options is:
[tex]\[ f^1(x) = \sqrt[3]{x} + 2 \][/tex]
### Verification
To ensure that this is correct, we can verify by composing [tex]\( f \)[/tex] and [tex]\( f^{-1} \)[/tex]:
- Compute [tex]\( f(f^{-1}(x)) \)[/tex]:
[tex]\[ f(f^{-1}(x)) = \left( \sqrt[3]{x} + 2 - 2 \right)^3 = (\sqrt[3]{x})^3 = x \][/tex]
- Compute [tex]\( f^{-1}(f(x)) \)[/tex]:
[tex]\[ f^{-1}(f(x)) = \sqrt[3]{(x - 2)^3} + 2 - 2 = x - 2 + 2 = x \][/tex]
Both compositions return the original variable [tex]\( x \)[/tex], confirming that the functions are indeed inverses of each other.
### Steps to Find the Inverse Function:
1. Replace [tex]\( f(x) \)[/tex] with [tex]\( y \)[/tex]:
[tex]\[ y = (x - 2)^3 \][/tex]
2. Solve for [tex]\( x \)[/tex] in terms of [tex]\( y \)[/tex]:
[tex]\[ y = (x - 2)^3 \][/tex]
3. To isolate [tex]\( x \)[/tex], take the cube root of both sides:
[tex]\[ \sqrt[3]{y} = x - 2 \][/tex]
4. Solve for [tex]\( x \)[/tex]:
[tex]\[ x = \sqrt[3]{y} + 2 \][/tex]
5. Replace [tex]\( y \)[/tex] with [tex]\( x \)[/tex] to write the inverse function:
[tex]\[ f^{-1}(x) = \sqrt[3]{x} + 2 \][/tex]
### Conclusion:
The inverse of the function [tex]\( f(x) = (x - 2)^3 \)[/tex] is:
[tex]\[ f^{-1}(x) = \sqrt[3]{x} + 2 \][/tex]
So the correct answer from the given options is:
[tex]\[ f^1(x) = \sqrt[3]{x} + 2 \][/tex]
### Verification
To ensure that this is correct, we can verify by composing [tex]\( f \)[/tex] and [tex]\( f^{-1} \)[/tex]:
- Compute [tex]\( f(f^{-1}(x)) \)[/tex]:
[tex]\[ f(f^{-1}(x)) = \left( \sqrt[3]{x} + 2 - 2 \right)^3 = (\sqrt[3]{x})^3 = x \][/tex]
- Compute [tex]\( f^{-1}(f(x)) \)[/tex]:
[tex]\[ f^{-1}(f(x)) = \sqrt[3]{(x - 2)^3} + 2 - 2 = x - 2 + 2 = x \][/tex]
Both compositions return the original variable [tex]\( x \)[/tex], confirming that the functions are indeed inverses of each other.
We hope our answers were helpful. Return anytime for more information and answers to any other questions you may have. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Get the answers you need at Westonci.ca. Stay informed with our latest expert advice.